Side deep placement of slow-release N as base fertilizer combined with urea as panicle fertilizer increases rice yield by optimizing dry matter and N accumulation and translocation - Hu, Mingming; Li, Zhixin; Chen, Kairui; Xiong, Ying; Luo, Yongheng; Wang, Ailing; Li, Leilei; Shu, Chuanhai; Chen, Zongkui; Yang, Zhiyuan; Sun, Yongjian; Ma, Jun (Frontiers in Plant Science, 2025)
IntroductionSide deep fertilization (SDF) technology and slow release N fertilizer offer advantages in enhancing rice yield and N use efficiency. However, the effects of side deep application of slow-release N as base fertilizer, combined with the application of urea at different growth stages, on dry matter accumulation, N uptake, translocation, assimilation, and yield formation in rice remain unclear.MethodsTherefore, in 2023 and 2024, a field experiment was conducted in Sichuan, China, using the local variety Chuankangyou 6308. Seven N treatments were established: no N (0N), conventional fertilization control (CK), 100% urea side deep placement (DU), 100% slow-release N fertilizer side deep placement (DSU), and DSU combined with 30% urea applied as basal fertilizer (DSU+U), tillering fertilizer (DSU+TU), or panicle fertilizer (DSU+PU). ResultsThe results showed that compared with CK, slow-release N fertilizer treatments significantly increased yield by 10.04%~23.28%, with DSU+PU having the highest yield, due to a higher number of effective panicles and seed-setting rate. DSU+PU is beneficial for increasing SPAD value and plant height, significantly increased total dry matter and N accumulation by 24.36% and 34.76%, respectively. The contribution rates of stem and leaf dry matter and N to yield increased by 9.67% and 4.40%, as well as 6.63% and 7.27%, respectively. Nitrate reductase (NR) and glutamine synthetase (GS) activities significantly increased by 4.88% and 6.86%, respectively. Notably, DSU+PU significantly improved N agronomic efficiency (NAE) and N fertilizer partial factor productivity (NPFP) by 89.00% and 23.27%, respectively. Meanwhile, DSU+PU reduced one fertilization application compared with CK and lowered N fertilizer costs compared with DSU.DiscussionIn conclusion, side deep placement of slow-release N as base fertilizer combined with urea as panicle fertilizer can delay leaf senescence, increase plant height and N metabolism enzyme activity, optimize dry matter and N accumulation and distribution, and significantly increase yield, and N use efficiency. It provides a solution for developing a simplified and efficient rice fertilization technology system based on the integration of agricultural machinery and agronomy.